Journal of Science in Medicine and Life - Journal of Science in Medicine and Life (Journal of Science in Medicine and Life, 2023)
Journal of Science in Medicine and Life - publishes peer-reviewed articles from various fields of medicine and life sciences, including original research, systematic reviews, special reports, case presentations, major medical breakthroughs and letters to the editor. The Journal focuses on current matters that lie at the intersection of biomedical science and clinical practice and strives to present this information to inform health care delivery and improve patient outcomes.